2015
DOI: 10.1177/1524838015622439
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal Strangulation as Part of Domestic Violence: A Review of Research

Abstract: This article reviews recent scholarship around the issue of nonfatal strangulation in cases of domestic violence. In the mid-1990s, the San Diego City Attorney's Office began a systematic study of attempted strangulation among 300 domestic violence cases, becoming one of the first systematic research studies to specifically examine the prevalence of attempted strangulation as a form of injury associated with ongoing domestic violence. Prior to this time, most of the research into strangulation was conducted po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(120 citation statements)
references
References 72 publications
2
115
1
Order By: Relevance
“…2 Fifteen review articles were found examining the existing literature, 11 of which were from a predominantly medical perspective. [55][56][57][58][59][60][61][62][63][64] There were also four reviews that considered the legal and social implications. 1,48,65,66 What does the literature tell us?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Fifteen review articles were found examining the existing literature, 11 of which were from a predominantly medical perspective. [55][56][57][58][59][60][61][62][63][64] There were also four reviews that considered the legal and social implications. 1,48,65,66 What does the literature tell us?…”
Section: Resultsmentioning
confidence: 99%
“…There was one case control trial . Fifteen review articles were found examining the existing literature, 11 of which were from a predominantly medical perspective . There were also four reviews that considered the legal and social implications …”
Section: Resultsmentioning
confidence: 99%
“…Finally, according to the FBI site for the SHR, NIBRS does not include drowning, pushed or thrown, or strangulation among the weapon types causing deaths, and the circumstances do not include sniper attacks, arguments over money or property, or Lover's triangles. Drowning and dying from being pushed or thrown are more likely to kill young children and the elderly (Huff‐Corzine et al., ), whereas strangulation is common among victims of intimate partner violence (Pritchard, Reckdenwald, & Nordham, ; Pritchard, Reckdenwald, Nordham, & Holton, ).…”
Section: Sources Of Official Data To Examine Mass Violencementioning
confidence: 99%
“…The victim may lose consciousness after only 10-15 seconds, and death may occur within 3-5 minutes. This dangerous form of violence is gendered, with males typically being the perpetrators of the violence and females being the victims (Nemeth, Bonomi, Lee, & Ludwin, 2012;Pritchard et al, 2017;Sorenson, Joshi, & Sivitz, 2014). The NONFATAL STRANGULATION AND COERCIVE CONTROL 3 expanding research base on strangulation was initiated by a study of 300 nonfatal strangulation victims, conducted by Strack et al (2001), which highlighted that 89% of the total sample had been victims of domestic violence.…”
Section: Nonfatal Strangulationmentioning
confidence: 99%
“…Finally, a negative consequence is instigated towards the victim (such as nonfatal strangulation) as a result of a previous threat to give credibility to future coercive control and to ensure that such acts are effective in asserting compliance (Dutton & NONFATAL STRANGULATION AND COERCIVE CONTROL 6 Goodman, 2005). In a case of nonfatal strangulation, restricting blood flow and ability to breathe with relatively little force shows the victim the ease with which the perpetrator can take their breath away, giving credibility to future threats (Nemeth et al, 2012;Pritchard, Reckdenwald, & Nordham, 2015;Thomas et al, 2014).…”
Section: Coercive Controlmentioning
confidence: 99%